European cinema: legacy of East, West, ethnicity and history - Elsaesser, Thomas (Monitor ISH, 2006)
European cinema in the past has been defined as the accumulation of individual national cinema. This essay process to invert the perspective, by putting forward the notion that each national cinemas is doubly occupied: by the memory of films from other national cinemas and, of course, by Hollywood movies. But such a state of "double occupancy" applies not only to cinema: every part of Europe, and all of our (national) identities are multiply defined, multiply experienced, and can be multiply assigned to us, at every point of our lives. Some of the films of the "New European Cinema" reflect this tension, and via the exploration of double occupancy return us to the historical origins of our present 'postnational' nationalisms.
Keywords: cinema; identity; ethnicity; etničnost; zgodovina; history; Europe; identiteta; film; evropski film